Pembubaran Perseroan Terbatas Berdasarkan Keputusan Rapat Umum Pemegang Saham (Rups) Di Indonesia Dan Australia - Lendrawati Lendrawati; Shelly Sonyatan (Journal of Judicial Review, 2014)
Considering a hefty amount of are left behind without being dissolved properly herein Indonesia may cause to many negative effects not only to the company but also the country and its government. Dissolving company is including the act of liquidating the company’s asset, businessman will prefer to establish a new company rather than to wind-up the company. Establishing a new company is more likely promising to businessman due to the time is faster than to wind up the company. Surprisingly, the above case rarely happen to the company in Australia, Australia has a commission called ASIC (Australian Securities and Investment Commission) which carry out two main functions, the administration and regulative functions. Every changes, addition or the company’s financial state must be reported to the commission. The presence of ASIC is believed to have facilitate and make winding up process easier.This research is carried to find out the process of winding-up and liquidation of a company, the obstacles, advantage and disadvantage in both country. This research is using a normative juridicial method of comparative law. Sources of data used in the form of primary, secondary and tertiary data. Data mining is done with library research. All data collected is then processed and analized, the qualitative analysis is used with the intention to classify aspects of data studied.Based on the results of this study showed that Australia has the best methods to wind up a company, which is proved by the presence of ASIC commission and the time duration.